IMPLEMENTATION OF GIS LOCATION DETERMINATION OF CATTLE IN ASAHAN REGENCY - Finkan Lady Anwar; Arridha Zikra Syah; Afrisawati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
Background: Cattle farming is one of the sources of food ingredients in the form of meat which has high economic value and is important in people's lives. There are many cattle breeders to go to to do the program every week or about 30 cattle farmers. The large number of cattle breeders makes it difficult for relevant agencies to map their locations. Method: This study uses qualitative methods in terms of data collection. Qualitative method is a method that focuses on understanding the overall aspect of the problem being discussed. Result: This research produces a system that can have the ability to map all cattle farms with an accurate distribution of locations. Conclusion: The application of GIS in this study allows the community to search for the location of cattle farms based on this application in Asahan and improve the quality of the mapping system of farm locations at the Livestock Service Office of Asahan Regency.